Vulvar Varicosities in an Adolescent Girl with Morbid Obesity: A Case Report - Aikaterini Giannouli; Vasiliki Rengina Tsinopoulou; Artemis Tsitsika; Efthimios Deligeoroglou; Flora Bacopoulou (MDPI AG, 2021)
Vulvar varicosities in nonpregnant females, either isolated or as a part of the pelvic congestion syndrome, are rare. We present a case of an adolescent girl with morbid obesity with bilateral bluish protrusions on the labia minora, as an incidental finding, that coincided with her excessive weight gain. The adolescent underwent thorough clinical examination, doppler ultrasound, contrast venography and varicography, and magnetic resonance angiography to rule out alternative diagnoses. Imaging results confirmed the presence of large venous lakes. Venous drainage to the internal iliac vein and connections with the long saphenous vein were delineated. Incompetence, dilatation, or reflux of ovarian or internal iliac veins, or their main tributaries, were not noted. Since the adolescent was asymptomatic and other pathologies, such as vascular malformations or hemangiomas were excluded, she was managed conservatively with counseling about lifestyle modification and weight reduction. This is only the third reported case of vulvar venous varicosities in adolescents. Female sex, along with obesity, are known risk factors for varicose vein formation; however, the pathogenesis is not fully understood. Additional research is needed to elucidate the role of excess adipose tissue in the pathophysiology of vulvar varicose veins and to optimize diagnostic workup and management in adolescence.